Analisis Q.S. Luqman [31]: 27- Mengungkap Keagungan Ilahi melalui Tasybih dengan Perspektif Tafsir Sufistik - Rizki Rahmadani; Akhmad Dasuki (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
Q.S. Luqman verse 27 is one of the Qur’anic verses that employs tashbih (simile) to illustrate the vastness of Allah’s knowledge and His divine majesty. The verse states that if all the trees on earth were pens and the seas were ink, they would not suffice to write the words of Allah. This study aims to analyze the structure of the simile in this verse and uncover its spiritual dimension through a Sufi interpretive approach. Using a qualitative library research method, primary sources include Sufi Qur’anic commentaries such as those of Al-Qushayri. The analysis reveals that the symbols of pens, ink, and the sea not only represent the boundlessness of divine knowledge but also convey esoteric meanings about the relationship between the servant and the Divine. Sufi interpretation emphasizes that Allah’s majesty cannot be grasped by reason alone, but rather through spiritual unveiling (kashf) and ma‘rifah (gnosis). Thus, the Sufi perspective enriches the understanding of this verse—not only literally, but also as a spiritual call toward deeper awareness of Allah’s infinite power and presence.